A sustainable revival process for defective LiFePO4 cathodes through the synergy of defect-targeted healing and in-situ construction of 3D-interconnected porous carbon networks. (1st March 2023) - Sun, Jing; Jiang, Zhenyu; Jia, Pingshan; Li, Su; Wang, Wenlong; Song, Zhanlong; Mao, Yanpeng; Zhao, Xiqiang; Zhou, Bingqian
Highlights: A novel strategy is proposed for the recycling and upgrading of defective LiFePO4 . Construction of 3d porous carbon coating facilitates Li-ion and electron transfer. Nitrogen can be doped to fabricate advanced rLFP@3dC-N nanohybrids. Reconstituted rLFP@3dC-N exhibits an extraordinary capacity recovery. Green closed-loop recycling strategy enables the sustainability of LIB industry. Abstract: The reutilization of spent cathode materials plays a key role in the sustainable development of Li-ion battery technology. However, current recycling approaches generally based on hydro-/pyrometallurgy fail to cater to Co-free cathodes ( e.g., LiFePO4, or LFP) owing to high consumption and secondary contamination. Here, a sustainable process is proposed for the revival of defective LFP cathodes through the synergy of defect-targeted healing and surface modification. Li deficiency and Fe oxidation of cathodes are precisely repaired by solution-based relithiation; meanwhile, 3D-interconnected porous carbon networks (3dC) are in-situ constructed with the intervention of salt template during annealing, which enhances the rate performance and electronic/ionic conductivity, by providing more convenient migration channels for Li ions and controlling carbon hybridization. Nitrogen is also doped via induction of urea to fabricate advanced nanohybrid rLFP@3dC-N. New cells using rLFP@3dC-N as cathode exhibit a reversible capacity of up to 169.74 and 141.79 mAh g −1 at 0.1 and 1C, respectively, with an excellent retention rate of over 95.7% at 1C after 200 cycles. Impressively, a high capacity of 107.18 mAh g −1 is retained at 5C. This novel concepts for Li replenishment and the construction of ion-transfer channels as well as conductive networks facilitate the regeneration of spent LFP and the optimization of its high-rate performance.